BRIlink as a Manifestation of Microeconomics - Asas, Fitria (Institut Agama Islam Al-Fatimah Bojonegoro, 2024)
BRIlink is a digital financial service initiated by Bank Rakyat Indonesia (BRI) to expand the reach of banking services, especially in areas that are not yet reached by conventional banks. As a manifestation of microeconomics, BRIlink shows how technology and innovation can empower communities and small businesses. The purpose of this writing is to see and explain how BRIlink is the embodiment of microeconomics in Indonesia. This research is a type of library research carried out by reading, reviewing, and analyzing various existing literature. The results are that BRIlink provides access to banking services and contributes significantly to strengthening the micro-economy by empowering individuals and small businesses, increasing financial inclusion, and encouraging local economic growth